Cryoballoon versus RF Ablation in Paroxysmal Atrial Fibrillation: Results from the German Ablation Registry. (17th October 2013) - SCHMIDT, MARTIN; DORWARTH, UWE; ANDRESEN, DIETRICH; BRACHMANN, JOHANNES; KUCK, KARL‐HEINZ; KUNISS, MALTE; LEWALTER, THORSTEN; SPITZER, STEFAN; WILLEMS, STEPHAN; SENGES, JOCHEN; JÜNGER, CLAUS; HOFFMANN, ELLEN
German Ablation Registry‐Different Energy Sources in AF Ablation Background Catheter ablation is used extensively with curative intention in atrial fibrillation. Radiofrequency ablation has long been a standard of care, while cryoballoon technology has emerged as a feasible approach with promising results. Prospective multicenter registry data referring to both ablation technologies in AF ablation therapy are lacking. Methods Between January 2007 and August 2011, a total of 3, 775 consecutive patients with symptomatic paroxysmal AF who underwent PV ablation in their respective centers were enrolled. The cohort was divided into 2 groups according to the ablation energy source used: cryoballoon ablation (group 1, n = 905 [24.0%], median age 63 years, 64.3% men) and RF ablation (group 2, n = 2870 [76.0%], median age 63 years, 62.7% men). Comorbidities and baseline clinical characteristics were similar in both groups. Results Acute success rate was similar in both groups (97.5% in cryo vs 97.6% in RF; P = 0.81). Procedure times were similar, ablation and fluoroscopy times were higher in cryoballoon when compared to RF ablation. Overall complication rate was similar in cryo‐ (4.6%) and RF‐ablation (4.6%; P = 1.0). Phrenic nerve palsy was more often in cryo versus RF ablation (2.1% in cryo vs 0.0% in RF; P < 0.001). Other complications were more common in RF compared to cryoablation (4.6% in RF vs 2.7% in cryo; P < 0.05). Conclusion RF ablation is the most widespread ablation method in Germany, but use of cryoballoon increased significantly. Procedure times were similar, but ablation and fluoroscopy times were longer in cryoballoon ablation. No significant differences were found in terms of acute success and overall complication rate.